Predictors of the Willingness to Promote Advance Care Planning among Nurses in Palliative Care Settings in Yogyakarta, Indonesia - Sari, Ike Wuri Winahyu; Hidayati, Rizqi Wahyu (Nurse Media Journal of Nursing, 2021)
Background: While previous studies showed that oncology nurses were highly inclined to promote advance care planning (ACP), there is a limited study focusing on ACP that concerns the willingness to promote ACP among palliative nurses in Indonesia. This issue needs to be investigated to determine the causative factors so that interventions for nurses can be arranged to improve ACP in Indonesia.Purpose: This study aimed to identify predictors of the willingness to promote ACP among nurses in palliative care settings.Methods: This study used a descriptive-analytical design with a cross-sectional approach. A total of 150 registered nurses with at least one year of experience were purposively recruited. Data were collected using the Indonesian version of the willingness to promote ACP instrument (I-WPACP) with a possible score range of 24 to 120; the higher the score, the higher the willingness to promote ACP. The descriptive statistic, independent t-test, Pearson correlation test, Spearman rank correlation test, and multiple linear regression test were used to analyze the data.Results: The willingness to promote ACP showed a mean score of 84.73Â±9.36. The score indicates a high willingness to promote ACP. The experience of receiving palliative care education became a related factor as well as the most closely related factor to the willingness to promote ACP in the palliative care settings (Î²=0.184; p=0.028).Conclusion: The willingness to promote ACP among nurses is high and closely related to their experience of receiving education about palliative care. Education about palliative care and training on ACP needs to be developed so that nurses can discuss ACP with patients and family caregivers.